Edward Curtis correspondence - Curtis, Edward, 1801-1856.
Correspondence of Curtis and Samuel B. Ruggles.
Lawyer and U.S. representative of New York.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ruggles, Samuel B. -- 1800-1881 -- Correspondence; Lawyers; Representatives, U.S. Congress -- New York (State)